STAGES OF SELECTION OF CONTROL TECHNOLOGY IN THE AUTOMATION OF THE CONTROL SYSTEM OF ROBOTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
A technologically advanced industry is at the heart of the country's development, and robotic automation is the key to this. Automation of industrial networks robots are a very useful and effective method for industrial development. Although the Republic of Uzbekistan is increasing its investment in industrial robots automation and control research, there are still many problems in the field of automation and control in application and I believe that there is still a certain gap between industrial robot technology and developed countries. On the one hand, it is serious the Republic of Uzbekistan hinders the development of industrial robotics, and on the other hand, it directly affects automation. Some of the Republic of Uzbekistan I believe that the main problems in industrial production, which have a very limiting effect on industrial development, are the oldness of the technological system. Therefore, it is important to pay attention to the value computer technology, automation control technology and sensor technology in the field of automation should be introduced. Industrial use Robots will be able to replace labor, reduce the intensity of operations and increase high labor productivity. In the technological system operational accuracy values are becoming important. It would not be wrong to say that scientific progress will bring the development process of industrial automation to a new stage. allowing fully automated production equipment to become mainstream and gradually replace manual operations. In recent years, the development of industrial automation has led to the development of a number of related industries, among which automation manipulators are based on one complete system based on an automated system. The development of manipulators as new automatic production line operating equipment can be huge and serves to increase the level of automation of production of enterprises and increase labor efficiency. this article examines the state of technological process development and researches have been cited that have investigated the optimal path of manipulators in automatic control engineering by integrating automated manipulators. If we want these technological processes to develop, we must ensure that the automation of processes in the industrial sectors of the Republic of Uzbekistan is controlled by technological processes and create opportunities for their activity.